Two new species of Phyllanthus (Phyllanthaceae) from Northern Minas Gerais, one with a distinctive anatomical character - Zavatin, Danilo Alvarenga; Ramos, Renato; Prado, Jefferson; Cordeiro, Inês; Soares, Marli Kasue Misaki; Appezzato-Da-Glória, Beatriz; Souza, Vinicius Castro; Orlandini, Priscila (Phytotaxa, 2025)
The flora of the Campos Rupestres has been increasingly studied in the municipality of Monte Azul, Minas Gerais, Brazil, a region considered a frontier of botanical knowledge, which has recently yielded new species. From this same area, we now describe two new species of Phyllanthus, along with the discovery of a distinctive anatomical trait in Phyllanthaceae: a thickened outer periclinal wall of the epidermis, rich in lipidic substances and forming pectic microchannels in one of the analyzed and described species. Although the two species are sympatric, they differ markedly in their morphological characters. Phyllanthus roseocalyx exhibits cylindrical phylloclades, distinctly pedicellate pistillate flowers, and staminate flowers with two stamens bearing horizontally dehiscent anthers. In contrast, Phyllanthus monteazulensis has flattened phylloclades, sessile pistillate flowers, and staminate flowers with three stamens and vertically dehiscent anthers. In addition, measurable characteristics of the phylloclades and flowers were used to compare the new species with other morphologically similar taxa of Phyllanthus that also bear phylloclades. This study includes morphological comparisons with similar species, a preliminary conservation assessment, illustrations, photographs, and distribution maps.